2019
DOI: 10.1016/j.ifset.2019.102190
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response of organic strawberries and kiwifruit subjected to PEF assisted-osmotic dehydration

Abstract: This research aims at evaluating the effect of pulsed electric field (PEF) pre-treatment before osmotic dehydration (OD) on physiological changes in organic strawberries and kiwifruits, in terms of metabolic heat production measured by isothermal calorimeter and of tissue damage evaluated by fluorescence microscopy, texture analysis and electrolytes leakage. Fruits pre-treated at two electric field strengths (100 and 200 V/cm) using 100 near-rectangular shaped pulses (pulse width: 10 μs, repetition time: 10 ms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
5
2
0
Order By: Relevance
“…Apple samples subjected to PEF at 125 V/cm and vacuum impregnation showed tial preservation of cell viability, while PEF at higher intensities (212.5 or 300 V/cm) bined with vacuum impregnation led to almost complete loss of cell viability (Figu This phenomenon was observed independently of the PEF position, before or after t process. These results are in line with those obtained by Tylewicz et al [52], who in gated the effect of PEF pre-treatment at 100 or 200 V/cm on the properties of fres osmotically dehydrated kiwi fruit. The researchers observed that PEF pre-treatment V/cm led to the partial preservation of cell viability of osmotically dehydrated fruit, higher PEF intensity (200 V/cm) caused cell death [52].…”
Section: Vacuum Impregnation Process Combined With Pef Treatment Of A...supporting
confidence: 92%
See 1 more Smart Citation
“…Apple samples subjected to PEF at 125 V/cm and vacuum impregnation showed tial preservation of cell viability, while PEF at higher intensities (212.5 or 300 V/cm) bined with vacuum impregnation led to almost complete loss of cell viability (Figu This phenomenon was observed independently of the PEF position, before or after t process. These results are in line with those obtained by Tylewicz et al [52], who in gated the effect of PEF pre-treatment at 100 or 200 V/cm on the properties of fres osmotically dehydrated kiwi fruit. The researchers observed that PEF pre-treatment V/cm led to the partial preservation of cell viability of osmotically dehydrated fruit, higher PEF intensity (200 V/cm) caused cell death [52].…”
Section: Vacuum Impregnation Process Combined With Pef Treatment Of A...supporting
confidence: 92%
“…These results are in line with those obtained by Tylewicz et al [52], who in gated the effect of PEF pre-treatment at 100 or 200 V/cm on the properties of fres osmotically dehydrated kiwi fruit. The researchers observed that PEF pre-treatment V/cm led to the partial preservation of cell viability of osmotically dehydrated fruit, higher PEF intensity (200 V/cm) caused cell death [52]. Similar behavior was observ the preservation of cell viability in the PEF pre-treated (100 or 200-400 V/cm) osmo drated strawberries [53].…”
Section: Vacuum Impregnation Process Combined With Pef Treatment Of A...supporting
confidence: 92%
“…The increasing energy input from 0.2 to 5.0 kJ/kg for tomatoes and from 0.6 to 12.6 kJ/kg for kiwi fruits leads to increased cell disruption up to 0.85 and 0.84, respectively. Previous studies have reported a similar relationship between PEF intensities and cell disintegration for the same investigated materials (Tylewicz et al, 2019;Andreou et al, 2020). The most intensive PEF treatments (5.0 and 12.6 kJ/kg) resulted in a CDI of 0.85 ± 0.02 for tomatoes and 0.84 ± 0.05 for kiwi fruits.…”
Section: Cell Disintegration Index (Cdi)supporting
confidence: 73%
“…Bearing in mind the measurement section of strawberry fruits (Figure 1), ten measurements from each sample group were taken. The texture was determined according to the modified method described by Tylewicz, Tappi, Genovese, Mozzon, and Rocculi [17]. Strawberry hardness was recorded by the penetration test with a Texture Analyzer (TA.HDi, Stable Microsystem Ltd., Godalming, UK), using a load cell of 5 kg and a stainless steel cylinder probe with a 2-mm diameter.…”
Section: Analysis Of Physicochemical Propertiesmentioning
confidence: 99%